Humanidades y docencia - Martínez, Elena (Revista Chilena de Humanidades, 2015)
Professor Elena Martínez relates her personal experience in the field of education to the significance which she sees in the high school and the university as active ,agents in the formation of the Chilean people. Her essay emphasizes the humanistic chamcter which shouJd inform every leve! of the educational system, as the proper means to find the true way of man, miented by the example of our great teachers.